Construction of a model for the development of social entrepreneurship based on innovation and technology transfer - Mukanova, Madina; Mukhamejanova, Aigul; Nurpeisova, Nazym; Zambinova, Zaure; Yeltayeva, Kuralay; Tugolbaeva, Daryika (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers social entrepreneurship in the Republic of Kazakhstan in the context of the national innovation ecosystem. The social entrepreneurship is becoming a tool for solving socio-economic problems. The task addressed in this study is to improve ways in order to increase the sustainability of social entrepreneurship through the effective use of its institutional and technological potential and the introduction of technology transfer mechanisms. The results have shown that social entrepreneurship has regional and sectoral inequalities, but its overall development dynamics demonstrate a steady growth. Correlation and regression analyses revealed that the relationship between the national development of social entrepreneurship and innovational and institutional factors was weak; that proved the complexity and non-homogeneity of the factors that have an impact on social business. In addition, the two-level model proposed suggests mechanisms for integrating social entrepreneurship into the national innovation environment and describes possible ways to improve the efficiency and economic effectiveness of social projects. The results involve providing the adaptive mechanisms for integrating social entrepreneurship with technological and institutional support systems. These, in turn, contribute to the formation of technological innovations, social entrepreneurship, innovatory solutions to social problems, efficiency, the scalability, and financial sustainability. The findings have shown that the implementation of a technology transfer model in the development of social entrepreneurship could promote the design of innovative platforms that create both an economic and social value.